Achievement of Educational Objectives by Senior Dental Students at the Department of Periodontology - Parviz Torkzaban; mahdi Kadkhodazadeh; Sepideh Seyedzadeh Sabou; Alireza Soltanian (Zanjan University of Medical Sciences and Health Services, 2017)
Background and objective: Periodical evaluation of educational curriculum is of great importance to know the strength and weakness, and thus success in education. Therefore, the aim of this study was to evaluate the accomplishment of educational objective and related factors in senior students of the periodontolgy department of dental school of Hamedan University of Medical Sciences in the year 2011-12. Materials and Methods: In this cross-sectional study 28 senior students attending the periodontology department participated in the study and their theoretical and practical knowledge were evaluated based on a prepared checklist and questionnaire. Data were collected and analyzed using Fisher's exact test. Results: According to the results, the educational objectives accomplished by senior students of the periodontology ward were desirable by %3.6, almost desirable by %60.7 and not desirable by %35.7. Achievement of educational objectives showed a correlation between sex and admission allotment (P<0.05). Conclusion: This study showed that the educational objective achievement by senior students of the periodontology department adding up desirable and almost desirable values was good by %64.3. Knowing the strength and weakness of the educational curriculum could be very useful to achieve educational goals. Keywords: Educational assessment, Dental student, Curriculum, Dental education.